Bioactivity and pharmacological potential of date palm (phoenix dactylifera L.) against Pandemic COVID‑19: a comprehensive review - Ahmad Mohd Zain, Muhammad Rajaei; Abdul Kari, Zulhisyam; A. O. Dawood, Mahmoud; Nik Ahmad Arif, Nik Shahman; Salmuna, Zeti Norfdiyati; Ismail, Norzila; Ibrahim, Al Hafz; Krishnan, Kumara Thevan; Che Mat, Nor Fazila; Edinur, Hisham Atan; Abdul Razab, Mohammad Khairul Azhar; Mohammed, Aurifullah; et al. (Springer, 2022)
A novel coronavirus disease (COVID-19) or severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2), transmitted from person to person, has quickly emerged as the pandemic responsible for the current global health crisis. This infection has been declared a global pandemic, resulting in a concerning number of deaths as well as complications post-infection, primarily among vulnerable groups particularly older people and those with multiple comorbidities. In this article, we review the most recent research on the role of date palm (Phoenix dactylifera L.) fruits (DPFs) to prevent or treat COVID-19 infection. The mechanisms underlying this preventive or therapeutic efect are also discussed in terms of bioactivity potentials in date palm, e.g., antimicrobial, antioxidant, anticancer, anti-diabetic, anti-infammatory, neuroprotective, and hemolytic potential, as well as prospect against COVID-19 disease and the potential product development. Therefore, it can be concluded that regular consumption of DPFs may be associated with a lower risk of some chronic diseases. Indeed, DPFs have been widely used in folk medicine since ancient times to treat a variety of health conditions, demonstrating the importance of DPFs as a nutraceutical and source of functional nourishment. This comprehensive review aims to summarize the majority of the research on DPFs in terms of nutrient content and biologically active components such as phenolic compounds, with an emphasis on their roles in improving overall health as well as the potential product development to ensure consumers’ satisfaction in a current pandemic situation. In conclusion, DPFs can be given to COVID19 patients as a safe and effective add-on medication or supplement in addition to routine treatments.